Kadar kolesistokinin laki-laki dewasa dengan konsumsi makanan siap saji khas Indonesia dan internasional - Inggita Kusumastuty; Dian Handayani; Rizky Ayu Diella Calista (Jurnal Gizi Klinik Indonesia, 2017)
Background: Fast food comes to a meal that is prepared fast and identically high in energy and fat contents since fast food is prepared using oil and fats. Excessive eating of fast food which is Indonesian typical fast foods and international fast foods will deliver obesity risk. Satiety and hunger are known as the two main keys to obesity prevention. Furthermore, Cholecystokinin (CCK) hormone is the one of bio-indicator that can indicate both satiety and hunger.Objective: The aim of this study is to determine the difference between CCK plasma level of Indonesian and international fast food.Method: A post-test only group design was done at 16 male adult subjects. This research measured CCK plasma of adult subjects with normal nutritional status whether consumed Indonesian typical fast foods and international fast foods. CCK plasma was measured by Enzyme-linked Immunosorbent Assay (ELISA) between 0-120 minutes.Results: Subjects who consumed Indonesian typical fast foods had significantly lower CCK plasma at 30,60 and 120 minutes measurement than that counterpart (p = 0.000).Conclusion: There is a different level of CCK after consuming Indonesian typical fast food and International fast food.